The general utility lattice program (GULP) - Gale, Julian; Rohl, Andrew (Taylor & Francis, 2003)
The General Utility Lattice Program (gulp) has been extended to include the ability to simulate polymers and surfaces, as well as adding many other new features, and the current status of the program is fully documented. Both the background theory is described, as well as providing a concise review of some of the previous applications in order to demonstrate the range of its use. Examples are presented of work performed using the new compatibilities of the software, including the calculation of Born effective charges, mechanical properties as a function of applied pressure, calculation of frequency-dependent dielectric data, surface reconstructions of calcite and the performance of a linear-scaling algorithm for bond-order potentials.